Laser sintering of cryogenically ground polymer powders into high-performance parts: The role of dry particle coating with a conductive flow agent. (9th January 2020) - Xi, Shuting; Zhang, Peiyao; Huang, Yajiang; Kong, Miqiu; Yang, Qi; Li, Guangxian
Abstract: The poor processability of cryogenically ground polymer powders rendered by their irregular shapes greatly hinders their applications in the selective laser sintering (SLS) technique. In this study, nonconductive silica (SiO2 ) nanoparticles and conductive carbon black (CB) nanoparticles were coated onto cryogenically ground polyamide 12 (PA12) powders and acted as flow agents to alleviate the flow problem. It was found that the addition of SiO2 or CB nanoparticles both greatly improved the flowability of cryogenically ground powders, thereby facilitating a successful sintering process. However, significantly improved mechanical performance and reduced structural defects were achieved only upon the addition of CB nanoparticles. The underlying mechanism was suggested to be related with the higher conductivity, lower friction, smaller adhesion energy and higher laser absorption efficiency of CB-coated powders. Therefore, conductive and radiation-adsorbing particles such as CB can serve as a multifunctional agent to enable the sintering of polymer powders with irregular shapes into parts with improved mechanical performance. Graphical abstract: Image 1090361 Highlights: Dry-particle coating improves the flowability of cryogenically ground PA12 powders. Coating powder with CB largely improves the mechanical properties of sintered parts. The mechanism is related with the conductive and radiation-adsorbing nature of CB.